Improved Tamarillo (Cyphomandra betacea Sendtn) Fruit Juice Quality with Carboxymethyl Cellulose Extracted from Cassava Peel (Manihot esculenta Crantz) - Emma Zaidar; Tiara Hidayanti (Journal of Chemical Natural Resources, 2023)
The utilization of Carboxymethyl Cellulose (CMC) from cassava peel (Manihot esculenta Crantz) through the quality of Tamarillo (Cyphomandra betacea Sendtn) juice was carried out through three stages. The first stage is Î±-cellulose isolation from cassava peel powder using an acid method and then comparing it with commercial cellulose using FTIR analysis. The second stage is an Î±-cellulose conversion into CMC by alkalization (using isopropanol and NaOH), carboxymethylation (using NaMCA), neutralization (using CH3COOH 90% and ethanol), purification (using distilled water followed by centrifugation and the addition of acetone which produces CMC with positive results), and then comparing isolated CMC with commercial CMC by using FTIR analysis. The last stage is Tamarillo fruit juice preparation with and without CMC addition. At this stage, the concentration of CMC was carried from 0%, 0.25%, 0.5%, 0.75%, 1%, and 1.25%. The resultant juice was analyzed for its quality by stability (letting it stand for 24 hours), pH (with a pH meter), viscosity (with an Ostwald viscometer), vitamin C content (using the iodimetry method), antioxidant activity (using the free radical scavenging method with a solution and using a UV-VIS spectrophotometer), and organoleptic (tests on 30 untrained panellists). The best results were obtained from Tamarillo juice containing 1.25% CMC, which has 73% stability, pH 4.49, viscosity of 77.79 cP, vitamin C content of 25.32 mg/100 g and antioxidant activity of 59%. Organoleptic test results showed that fruit juice with the addition of 0.75% CMC was the most preferred result by panellists based on aroma, taste, texture, and color.